Internal quantum efficiency of AlGaN/AlN quantum dot superlattices for electron-pumped ultraviolet sources. (5th October 2020) - Harikumar, A; Donatini, F; Bougerol, C; Bellet-Amalric, E; Thai, Q -M; Dujardin, C; Dimkou, I; Purcell, S T; Monroy, E
Abstract: In this paper, we describe the growth and characterization of ≍530 nm thick superlattices (100 periods) of Alx Ga1-x N/AlN (0 ⩽ x ⩽ 0.1) Stranski–Krastanov quantum dots (QDs) for application as the active region of electron-beam pumped ultraviolet lamps. Highly dense (>10 11 cm −2 ) QD layers are deposited by molecular beam epitaxy, and we explore the effect of the III/V ratio during the growth process on their optical performance. The study considers structures emitting in the 244–335 nm range at room temperature, with a relative linewidth in the 6%–11% range, mainly due to the QD diameter dispersion inherent in self-assembled growth. Under electron pumping, the emission efficiency remains constant for acceleration voltages below ≍9 kV. The correlation of this threshold with the total thickness of the SL and the penetration depth of the electron beam confirms the homogeneity of the nanostructures along the growth axis. Below the threshold, the emission intensity scales linearly with the injected current. The internal quantum efficiency (IQE) is characterized at low injection, which reveals the material properties in terms of non-radiative processes, and high injection, which emulates carrier injection in operation conditions. In QDs synthesized with III/V ratio <0.75, the IQE remains around 50% from low injection to pumping power densities as high as 200 kW cm −2, being the first kind of nanostructure that present such stable behaviour.